Kontribusi kemampuan manajerial kepala sekolah, motivasi guru, dan lingkungan kerja terhadap kinerja guru sekolah dasar se-Kecamatan Galur Kulon Progo - Riesti Cahyaningrum; Ag. Sri Purnami (Tuladha : Jurnal Pendidikan Dasar, 2022)
The objectives of this study include: (1) To determine the contribution of principals' managerial abilities, teacher motivation, and work environment to the performance of elementary school teachers in Galur Kulon Progo Subdistrict, (2) To determine the principal managerial ability's contribution to the performance of elementary school teachers District of Kulon Progo Line; (3) To find out the contribution of teacher motivation to the performance of elementary school teachers in Galur Kulon Progo District; and (4) To find out the contribution of the work environment to the performance of elementary school teachers in Galur Kulon Progo District. This research is quantitative research. The variables of this study are teacher performance, managerial principals, teacher motivation, and work environment. The population in the study were all elementary school teachers in Galur Kulon Progo District. The sampling technique in this study used a proportional random sampling technique so that there were 162 teachers. The analysis used is multiple linear regression analysis. Based on the results of data analysis, conclusions were obtained: (1) Principal managerial ability, teacher motivation, and work environment contributed positively by 50.16% to the performance of elementary school teachers in Galur Kulon Progo District; (2) Principal managerial abilities contribute positively to 12.69% to the performance of elementary school teachers in Galur Kulon Progo District; (3) Motivation of teachers contributes 21.01% positively to the performance of elementary school teachers in Galur Kulon Progo District; and (4) The work environment contributes positively to 16.45% to the performance of elementary school teachers in Galur Kulon Progo Sub-district.